Big Data Analytics Proceedings of CSI 2015 - Aggarwal, V. B.; Bhatnagar, Vasudha; Mishra, Durgesh Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume comprises the select proceedings of the annual convention of the Computer Society of India. Divided into 10 topical volumes, the proceedings present papers on state-of-the-art research, surveys, and succinct reviews. The volumes cover diverse topics ranging from communications networks to big data analytics, and from system architecture to cyber security. This volume focuses on Big Data Analytics. The contents of this book will be useful to researchers and students alike.
Title of the Papers along with the Name of the Authors -- Need for Developing Intelligent Interfaces for Big Data Analytics in the Micro Finance Industry -- Unified Resource Descriptor over KAAS Framework Refining Cloud Dynamics -- An Adoptable and Secure Intelligent Smart Card Framework for Internet of Things and Cloud Computing -- A Framework for Ontology Learning from Taxonomic Data -- Leveraging Map-Reduce with Column Oriented Stores: Study of Solutions and Benefits -- Hadoop: Solution to Unstructured Data Handling -- Task Based Load Balancing Algorithm by Efficient Utilization of VMs in Cloud Computing -- A Load Balancing Algorithm Based on Processing Capacities of VMs in Cloud Computing -- Package Based Approach for Load Balancing in Cloud Computing -- Workload Prediction of e-Business Websites on Cloud Using Different Methods of ANN -- Data Security in Cloud Based Analytics -- Ontology Based Ranking in Search Engine -- Hidden Data extraction Using URL Templates Processing -- Automatic Generation of Ontology for Extracting Hidden Web Pages -- Importance of SLA in Cloud Computing -- A Survey on Cloud Computing -- Adapting & Reducing Cost in Cloud Paradigm (ARCCP) -- Power Aware Based Workflow Model of Grid Computing Using Ant Based Heuristic Approach -- Image Categorization Using Improved Data Mining Technique -- An Effective Hybrid Encryption Algorithm for Ensuring Cloud Data Security -- Big Data Analytics: Recent and Emerging Application in Services Industry -- An Analysis of Resource Aware Adaptive Scheduling for HPC Clusters with Hadoop -- Analytical and Perspective Approach of Big Data in Cloud Computing -- Implementation of CouchDB Views -- Evolution of FOAF and SIOC in Semantic Web: A Survey -- Classification of e-Commerce Products Using Rep-Tree And K-Mean Hybrid Approach -- A Study of Factors Affecting MapReduce Scheduling -- Outlier Detection in Agriculture Domain: Application and Techniques -- A Framework for Twitter Data Analysis -- Web Structure Mining Algorithms: A Survey -- Big Data Analytics via IoT with Cloud Service -- A Proposed Contextual Model for Big Data Analysis Using Advanced Analytics -- Ranked Search over Encrypted Cloud Data in Azure Using Secure kNN -- DCI3 Model for Privacy Preserving in Big Data -- Study of Sentiment Analysis Using Hadoop -- OPTIMA(OPinionated Tweet Implied Mining and Analysis) - An Innovative Tool to Automate Sentiment Analysis -- Mobile Agent Based MapReduce Framework for Big Data Processing -- Review of Parallel Apriori Algorithm on Map Reduce Framework for Performance Enhancement -- A Novel Approach to Realize Internet of Intelligent Things -- An Innovative Approach of Web Page Ranking Using Hadoop and MapReduce Based Cloud Framework -- SAASQUAL: A Quality Model for Evaluating SaaS on the Cloud Computing Environment -- Scalable Aspect Based Summarization in the Hadoop Environment -- Parallel Mining of Frequent Itemsets from Memory Mapped Files -- Handling Smurfing Through Big Data -- A Novel Approach for Semantic Prefetching Using Semantic Information and Semantic Association -- Optimized Cost Model with Optimal Resource Usage for Cloud -- Understanding Live Migration Techniques Intended for Resource Interference Minimization in Virtualized Cloud Environment -- Cloud Security Issues and Challenges -- A Novel Approach to Protect Cloud Environments Against DDOS Attacks -- An Approach for Workflow Scheduling in Cloud Using ACO -- Data Type Identification and Extension Validator Framework Model for Public Cloud Storage -- Robust Fuzzy Neuro System for Big Data Analytics -- Deployment of Cloud Using Open Source Virtualization: Study of VM Migration Methods and Benefits -- Implementation of Category-wise Focused Web Crawler -- MAYA: An Approach for Energy and Cost Optimization for Mobile Cloud Computing Environments -- Load Balancing in Cloud - A Systematic Review -- Cloud-Based Big Data Analytics - A Survey of Current Research and Future Directions -- Fully Homomorphic Encryption Scheme with Probabilistic Encryption Based on Euler'sTheorem and Application in Cloud Computing -- Big Data: Issues, Challenges and Techniques in Business Intelligence -- Cloud Computing in Bioinformatics and Big Data Analytics: Current Status and Future Research -- Generalized Query Processing Mechanism in CDBMS -- Deliberative Study of Security Issues in Cloud Computing -- Green Cloud Computing: An Overview -- Literature Review of QoS with Load Balancing in Cloud Computing Environment -- WAMLB: Weighted Active Monitoring Load Balancing in Cloud Computing -- Applications of Attribute Based Encryption in Cloud Computing Environment -- Query Optimization: Issues and Challenges in Mining of Distributed Data -- Comprehensive Study of Cloud Computing and Related Security Issues -- Healthcare Data Analysis Using R and MongoDB -- Data Mining Tools and Techniques for Mining Software Repositories: A Systematic Review -- SWOT Analysis of Cloud Computing Environment -- A Review on Quality of Service in Cloud Computing -- Association Rule Mining for Finding Admission Tendency of Engineering Student with Pattern Growth Appraoch -- Integrated Effect of Nearest Neighbors and Distance Measures in k-NN Algorithm.
Keywords: Data mining; Computational intelligence; Quantitative research; Information technology -- Management; Quality of life; Data Mining and Knowledge Discovery; Computational Intelligence; Data Analysis and Big Data; Computer Application in Administrative Data Processing; Quality of Life Research